An organocatalyst bound α-aminoalkyl radical intermediate for controlled aerobic oxidation of iminium ions. Issue 28 (27th June 2018) - Motaleb, Abdul; Bera, Asish; Maity, Pradip
Abstract : A nucleophilic catalyst is introduced for facile radical formation and its catalyst controlled aerobic oxidation. Abstract : A catalyst bound α-aminoalkyl radical intermediate from iminium is developed to control its formation and reactivity with aerobic oxygen. The influence of the catalyst was demonstrated via the ease of radical intermediate formation and its subsequent reactivity, including the first catalyst-controlled enantioselective aerobic oxidation with a chiral phosphite catalyst.